THE QUALITY OF SERVICE AT PT. AIR MINUM SANGGAM BALANGAN (PERSERODA) IN PARINGIN SUB-DISTRICT - Siti Paulina (PPPM STIA Amuntai, 2025)
This study aims to evaluate the quality of public services at PT. Air Minum Sanggam Balangan (Perseroda) in Paringin District, Balangan Regency. A descriptive qualitative approach was employed, with data collected through observation, in-depth interviews, and documentation. The analysis is based on Fitzsimmons' five service quality dimensions: tangible, reliability, responsiveness, assurance, and empathy. The results indicate that overall service quality falls under the “fair” category. The dimensions of reliability, assurance, and empathy show positive performance, particularly in terms of procedural accuracy, staff attitude, and responsiveness to customer needs. However, weaknesses were identified in the responsiveness and tangible dimensions, especially regarding slow responses to customer complaints and limited technical facilities, such as the absence of backup generators. This study recommends improvements in technical infrastructure and response speed to enhance the overall quality of public services.